Pengaruh Gaya Hidup, Persepsi Harga, dan Promosi terhadap Minat Beli Produk Kosmetik Emina di Kabupaten Nganjuk - Nurul Ririn Komariyah; Dyah Suswanti Respatiningtias; Indrian Supheni (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of lifestyle, price perception, and promotion on the purchase intention of Emina cosmetic products on the Shopee e-commerce platform among consumers in Sonobekel Village, Tanjunganom District, Nganjuk Regency. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 96 respondents selected using purposive sampling. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-test and F-test with the assistance of SPSS version 30. The results show that partially, lifestyle, price perception, and promotion each have a positive and significant effect on purchase intention. Simultaneously, these three variables also have a positive and significant effect on purchase intention. These findings highlight that marketing strategies combining target consumers’ lifestyle alignment, fair price perception, and effective promotions can enhance purchase intention for Emina cosmetic products on Shopee.